Perancangan Sistem Promosi Berbasis OpenCart untuk Meningkatkan Penjualan Produk UMKM Oleh-Oleh Khas Minangkabau di Kecamatan VII Koto Sungai Sariak - Hadai Yani Fitri, Gina; Annas, Firdaus; Aulia, Selvina (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Micro, small, and medium enterprises (MSMEs) play an important role in the local economy, especially in the production of Minangkabau souvenirs, such as traditional foods that attract tourists. However, MSMEs in Kecamatan VII Koto Sungai Sariak still market their Minangkabau souvenir products traditionally through physical stores, which can limit market reach and the potential for increased sales. This condition can actually be overcome by utilizing technological advances, namely by developing a digital-based promotion system to expand access to the global market. This research aims to design a web-based promotion system using the OpenCart platform designed to support the marketing of typical Minangkabau souvenir products by MSMEs in District VII Koto Sungai Sariak. This research uses a Research and Development (R&D) methodology with a 4D approach consisting of four stages: Define, Design, Develop, and Disseminate. The Define stage involved needs analysis through interviews and observations to identify traditional marketing problems. At the Design stage, the system was designed by incorporating the features needed to digitize the marketing process of typical Minangkabau souvenir products. At the Develop stage, OpenCart was used to create a prototype of the system, which was then validated for validity and usability. Then the Disseminate stage involves the implementation and evaluation of the system among MSME players to measure its effectiveness in increasing sales. The results showed that the designed OpenCart-based promotion system is valid, practical, and effective in increasing the marketability of MSME products. The research findings indicate that MSMEs in Kecamatan VII Koto Sungai Sariak can use digital platforms such as OpenCart to strategically overcome conventional marketing barriers and improve the competitiveness of Minangkabau souvenir products in the international market. Overall, by maximizing technology in product promotion, this approach helps MSMEs deal with difficulties in the face of globalization and drives local economic progress.